1942
DOI: 10.1093/genetics/27.6.619
|View full text |Cite
|
Sign up to set email alerts
|

Diploid-Tetraploid Periclinal Chimeras as Bud Variants in Citrus

Abstract: INTRODUCTIOKUMEROUS genetic variations affecting portions of Citrus trees have N occurred under cultivation. "Bud-variation" or "bud-mutation" forms have been studied extensively from the horticultural viewpoint in various commercial varieties, such as the Eureka and Lisbon lemons (SHAMEL et al. 1936), but little is known about the causation of the changes concerned.Certain conspicuously mixed bud-variation forms, such as lemon "strains'' with white-margined leaves (SHAMEL 1932) and orange strains with two ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1948
1948
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In this study, total DNA was extracted from whole intact leaves, since the epidermis of the leaf came from L1 and the mesophyll came from L2 and L3 (Frost and Krug, 1942;Tilney-Bassett, 1986). However, the fruits of HH were divided…”
Section: Discussionmentioning
confidence: 99%
“…In this study, total DNA was extracted from whole intact leaves, since the epidermis of the leaf came from L1 and the mesophyll came from L2 and L3 (Frost and Krug, 1942;Tilney-Bassett, 1986). However, the fruits of HH were divided…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by Yahata et al (2005), who reported that there was no difference in stomata size among doubled haploid and cytochimeras (1 x ‐2 x and 2 x ‐4 x ). According to Frost and Krug (1942), in plant leaves, the first germ layer is responsible for the formation of the epidermis and the second germ layer is associated with the formation of the internal leaf tissues such as the procambium and the vascular tissue. Thus, those cytochimera having octoploid guard cells might be associated with the octoploid level of layer I (Dermen and Bain, 1944; Thao et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Tree architecture, in turn, depends upon many anatomical and physiological factors including the arrangement and organization of the apical and axillary meristems. In addition, plant meristems are stratified structures generally consisting of three different cell layers, as those found in citrus (Frost & Krug, 1942), giving rise to separate tissues. These layers may accumulate mutations independently generating clonally diverse cell lineages that form chimeric organs with distinct proportions of the mutated alleles, a circumstance that may hamper the determination of mutations rates.…”
mentioning
confidence: 99%